2018
DOI: 10.1208/s12249-018-1030-3
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Topical 48-H Release Formulation as an Anti-scarring Treatment for Deep Partial-Thickness Burns

Abstract: The purpose of this study was to develop pirfenidone (PF) ointment formulations for a dose finding study in the prophylactic treatment of deep partial-thickness burns in a mouse model. A preformulation study was performed to evaluate the solubility of PF in buffers and different solvents and its stability. Three different formulations containing 1, 3.5, and 6.5% w/w PF were prepared and optimized for their composition for testing in mice. Optimized formulations showed promising in vitro release profiles, in wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Pirfenidone is an FDA-approved antifibrotic drug for the treatment of idiopathic pulmonary fibrosis. A mouse model of deep partial thickness burns revealed the antiinflammatory effect of pirfenidone [28,29]. Further experimental burn studies confirmed that the application of pirfenidone on cutaneous burn wound sites has an excellent scarreducing effect [27].…”
Section: Antiscarring Strategiesmentioning
confidence: 82%
“…Pirfenidone is an FDA-approved antifibrotic drug for the treatment of idiopathic pulmonary fibrosis. A mouse model of deep partial thickness burns revealed the antiinflammatory effect of pirfenidone [28,29]. Further experimental burn studies confirmed that the application of pirfenidone on cutaneous burn wound sites has an excellent scarreducing effect [27].…”
Section: Antiscarring Strategiesmentioning
confidence: 82%
“…Pirfenidone has also been shown to reduce proliferation and inhibit epithelial-mesenchymal transition in keloid keratinocytes [ 137 ] . In wound healing studies, pirfenidone has been shown to reduce pro-inflammatory cytokine production, neutrophil infiltration, and collagen synthesis [ 138 , 139 ] , and in a clinical trial topical application of an 8% pirfenidone gel induced scar regression to a greater degree than control pressure therapy in burn-induced HTS in pediatric patients [ 140 ] .…”
Section: Therapeutic Strategies To Prevent Scar Formationmentioning
confidence: 99%
“…For example, proinflammatory cytokine IL‐6 and IL‐8 enhanced scarring and the anti‐inflammatory cytokine IL‐10 has the opposite effect . Therefore, upregulating anti‐inflammatory cytokine and reducing pro‐inflammatory cytokine could inhibit HSs formation, as found in some TCM, such as bupleurum and pirfenidone ointment . Recently, a breakthrough study showed that adipocytes are regenerated from myofibroblasts by activating the adipocyte transcription factors during wound healing.…”
Section: Biotherapy For Inflammation In Hssmentioning
confidence: 99%
“…89 Therefore, upregulating anti-inflammatory cytokine and reducing pro-inflammatory cytokine could inhibit HSs formation, as found in some TCM, such as bupleurum 90,91 and pirfenidone ointment. 92 Recently, a breakthrough study showed that adipocytes are regenerated from myofibroblasts by activating the adipocyte transcription factors during wound healing. The consequential effect was triggered by BMP signalling from the actively growing hair follicles, and the findings fortify the importance of BMPs in the transdifferentiation of myofibroblasts and adipocytes.…”
Section: Biotherapy For Inflammation In Hssmentioning
confidence: 99%